2022
DOI: 10.1021/acs.jmedchem.2c01349
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Uptake Relationship Studies of Oxazolidinones in Gram-Negative ESKAPE Pathogens

Abstract: The clinical success of linezolid for treating Gram-positive infections paired with the high conservation of bacterial ribosomes predicts that if oxazolidinones were engineered to accumulate in Gram-negative bacteria, then this pharmacological class would find broad utility in eradicating infections. Here, we report an investigative study of a strategically designed library of oxazolidinones to determine the effects of molecular structure on accumulation and biological activity. Escherichia coli, Acinetobacter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…83 Recently, Duerfeldt et al reported a library of oxazolidinone derivatives developed against ESKAPE bacteria. 84 The drug designing direction focused on increasing the accumulation of the new analogues in Gram-negative bacteria by circumventing efflux and increasing their ability to penetrate membranes. The structural modifications focused on the C-ring and a large number of compounds were synthesized and evaluated against wild-type E. coli, A. baumannii, and P. aeruginosa, and isogenic mutants with different grades of efficiency of the outer membrane and/or efflux pump.…”
Section: Insert Figure 10 Herementioning
confidence: 99%
See 1 more Smart Citation
“…83 Recently, Duerfeldt et al reported a library of oxazolidinone derivatives developed against ESKAPE bacteria. 84 The drug designing direction focused on increasing the accumulation of the new analogues in Gram-negative bacteria by circumventing efflux and increasing their ability to penetrate membranes. The structural modifications focused on the C-ring and a large number of compounds were synthesized and evaluated against wild-type E. coli, A. baumannii, and P. aeruginosa, and isogenic mutants with different grades of efficiency of the outer membrane and/or efflux pump.…”
Section: Insert Figure 10 Herementioning
confidence: 99%
“…These results highlight how small structural modifications can broaden the spectrum of action of oxazolidinones against Gram-negative bacteria. 84 …”
Section: Oxazolidinones As Antibacterial Agentsmentioning
confidence: 99%
“…We have recently leveraged the well-established oxazolidinone SAR trends to identify motif-driven enhancement in Gram-negative permeation and accumulation. 52 Using a reagent clustering and selection approach, a chemically diverse library of oxazolidinones was synthesized and assessed for activity against three ESKAPE pathogens, E. coli, P. aeruginosa, and A. baumannii, with varying levels of barrier compromise (i.e., efflux deletion and/or OM hyperporination). Orientation, location, and composition of functional groups were all determinants of chemotype accumulation.…”
Section: Structure−uptake Relationshipsmentioning
confidence: 99%
“…The high conservation between Gram-positive and Gram-negative ribosomes, however, implies that if oxazolidinone analogs could accumulate and avoid efflux, this family would exhibit broad-spectrum activity. We have recently leveraged the well-established oxazolidinone SAR trends to identify motif-driven enhancement in Gram-negative permeation and accumulation . Using a reagent clustering and selection approach, a chemically diverse library of oxazolidinones was synthesized and assessed for activity against three ESKAPE pathogens, E. coli , P. aeruginosa , and A. baumannii , with varying levels of barrier compromise (i.e., efflux deletion and/or OM hyperporination).…”
Section: Structure–uptake Relationshipsmentioning
confidence: 99%
“…Recently, to aid in the discovery of Gram-negative antibiotics, rules of entry for Gram-negative bacteria, derived from evaluation of EC OM-penetrating drugs, have been established, which are (i) molecular weight <500 g/mol; (ii) cLogD 7.4 between −2 and 0; (iii) ≤5 rotatable bonds; (iv) high polar surface area (average 165 Å); (v) low globularity; and (vi) presence of a 1° amine or guanidinium. While these rules do translate to other Gram-negative pathogens like Acinetobacter baumannii, PA has proven to be much more limited in chemical motifs that promote accumulation . Evaluation of the compounds in this series with regard to the entry rules would indicate that none in the series readily cross the OM of PA (Table S2).…”
mentioning
confidence: 99%